Inelastic buildings with tuned mass dampers under moderate ground motions from distant earthquakes. - Lukkunaprasit, P. (Earthquake engineering & structural dynamics.)
The effectiveness of tuned mass dampers (TMD) in vibration control of buildings was investigated under moderate ground shaking caused by long distance earthquakes with frequency contents resembling the 1985 Mexico City (SCT) or the 1995 Bangkok ground motion. The elastic perfectly plastic material behaviour was assumed for the main structure, with linear TMDs employed by virtue of their simplicity and robustness. The accumulated hysteretic energy dissipation affected by TMD was examined and the ratio of the hysteretic energy absorption in the structure with TMD to that without it is proposed to be used, in conjunction with the peak displacement ratio, as a supplementary TMD performance index since it gives an indication of the accumulated damage induced in the inelastic structures. For the ground motions considered, TMD would be effective in reducing the hysteretic energy absorption demand in the critical storeys for buildings in the 1.8-2.8 s range. The consequence is reduction in damage of the buildings which would otherwise suffer heavy damage in the absence of TMD, resulting in economical restorability in the damage control limit state. This is of practical significance in view of the current trend toward performance based design.